A preliminary study of nitrate concentration in soil and well waters from agricultural and non-agricultural lands / Norhayati Mohd Tahir, Suhaimi Suratman and Roselina Abdul Aziz - Mohd Tahir, Norhayati; Suratman, Suhaimi; Abdul Aziz, Roselina (2004)
A preliminary study has been carried to determine the nitrate distribution in soils and well waters located in Batu Rakit - Kuala Nerus district of Terengganu. Main objective of the study is to evaluate the impact of agricultural activities on levels of nitrate in the study area. A total of four locations were chosen covering four different soil types. At each location, soils were sampled from two sites, each representing an agricultural and non-agricultural site. Wen water was also collected at two sites per sampling location representing agricultural and non-agricultural sites. Nitrate content in soil and water was determined using ion chromatography. In addition, the pH of soils and well waters were also determined using pre-calibrated pH meter in the laboratory and at the site, respectively. Results obtained suggest that agricultural sites exhibit a marginally higher nitrate concentration than the non-agricultural sites but no clear trend with depth could be observed for both types of land use. In the case of soil pH, although results obtained suggest some variations in soil pH with depth particularly in the cultivated land, statistically, these variations are insignificant. None the less, comparison of the data suggests that types of-soils could to some extent play a role in controlling the concentrations of nitrate and pH values in soils. However, the trend in well water is not obvious where no clear influence of agricultural activities and soil types could be discerned on the levels of nitrate and pH in the water.